2022
DOI: 10.1080/14459795.2022.2114526
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the impact of the COVID-19 pandemic on problematic gambling and gaming: an international key informant survey

Abstract: This paper reports a qualitative survey of experts in problem gaming and/or problem gambling from 19 countries worldwide on the impact of the COVID-19 pandemic on problematic gaming and gambling. Twenty-seven problem gaming experts reported (i) no licensing changes, (ii) few existing or newly introduced policies or regulations, (iii) overall increases in gaming, (iv) adverse healthrelated outcomes, (v) media coverage of gaming and eSports, (vi) limited health service capacity for treatment and prevention, (vii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In particular, with the outbreak of the COVID-19 pandemic, studies in Asian countries such as China and India reported an increase in Internet addiction at mild and moderate levels that was related to increased depression and anxiety [ 2 , 3 ]. Research has been conducted in several countries on the increase in digital media screen time and related mental/behavioral and physical health problems during the COVID-19 pandemic [ 4 , 5 ]. Increases in screen time, decreases in physical activity, and sleep problems were especially common in children and adolescents [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, with the outbreak of the COVID-19 pandemic, studies in Asian countries such as China and India reported an increase in Internet addiction at mild and moderate levels that was related to increased depression and anxiety [ 2 , 3 ]. Research has been conducted in several countries on the increase in digital media screen time and related mental/behavioral and physical health problems during the COVID-19 pandemic [ 4 , 5 ]. Increases in screen time, decreases in physical activity, and sleep problems were especially common in children and adolescents [ 6 ].…”
Section: Introductionmentioning
confidence: 99%